Early Life Exposure to Tumor Necrosis Factor Induces Precocious Sensorimotor Reflexes Acquisition and Increases Locomotor Activity During Mouse Postnatal Development - Paraschivescu, Cristina; Barbosa, Susana; Van Steenwinckel, Juliette; Gressens, Pierre; Glaichenhaus, Nicolas; Davidovic, Laetitia (Frontiers in Behavioral Neuroscience, 2022)
Inflammation appears as a cardinal mediator of the deleterious effect of early-life stress exposure on neurodevelopment. More generally, immune activation during the perinatal period, and most importantly elevations of pro-inflammatory cytokines levels could contribute to psychopathology and neurological deficits later in life. Cytokines are also required for normal brain function in homeostatic conditions and play a role in neurodevelopmental processes. Despite these latter studies, whether pro-inflammatory cytokines such as Tumor Necrosis Factor (TNF) impact neurodevelopmental trajectories and behaviour during the immediate postnatal period remains to be elucidated. To address this issue, we have injected mouse pups daily with recombinant TNF from postnatal day (P)1 to P5. This yielded a robust increase in peripheral and central TNF at P5, and also an increase of additional pro-inflammatory cytokines. Compared to control pups injected with saline, mice injected with TNF acquired the righting and the acoustic startle reflexes more rapidly and exhibited increased locomotor activity two weeks after birth. Our results extend previous work restricted to adult behaviours and support the notion that cytokines, and notably TNF, modulate early neurodevelopmental trajectories.